Dialectic of Consumerism: How A Series of Unfortunate Events Defies Itself - Hill, Renae Chalaine (URJ-UCCS: Undergraduate Research Journal at UCCS, 2014)
Contemporary American culture is steeped in consumerist ideology. It is a social climate where profit rules and control of cultural production is limited to a select few corporate interests. As such, popular culture is designed to reinforce consumerist values in order to keep wealth and power concentrated at the upper echelons of the social hierarchy, keeping the middle class oppressed. This paper seeks to explore ways in which a seemingly subversive text reifies hegemonic ideology within the dominant societal discourse. A rhetorical critical discourse analysis of the first three books of Daniel Handler’s A Series of Unfortunate Events reveals that despite the author’s intent to subvert consumerist ideology rooted in the Victorian sensibility, as a product of popular culture, the text adheres to the dominant discourse. In covert ways, it enforces consumerist values by perpetuating the myth that the upper class lifestyle is normative and desirable, that happiness is found in materialism, and that poverty is necessarily villainous and disgusting.